Macroglossia after Removeal of a Tumor of the Posterior Cranial Fossa. A Case Report - V. Yu. Ivanova; L. M. Tsentsiper; I. S. Terekhov; O. Yu. Razmologova; A. N. Kondratyev (Вестник анестезиологии и реаниматологии)
Postoperative macroglossia (PM) is a rather rare complication after craniofacial operations. The largest number of observations relate to neurosurgery especially in children. Prevention of risk factors, such as mechanical compression of the tongue, improper position on the operating table allows minimizing the amount and intensity of PM. The article presents a case when PM was the first symptom of dysgemic disorders in the brain stem.